Heterochromatin variation in chromosomes of Anopheles (Nyssorhynchus) darlingi Root and A.(N.) nuneztovari Gabaldón (Diptera: Culicidae) - Míriam Silva Rafael; Wanderli Pedro Tadei (Genetics and Molecular Biology, 2000)
C-banding was used to study the variations in heterochromatic block markings in chromosomes of Anopheles darlingi and A. nuneztovari from Manaus, State of Amazonas, and Macapá, State of Amapá, Brazil. Both species had two differently shaped X chromosomes and a Y chromosome that was entirely heterochromatic. The X1 chromosome of A. darlingi had markings that extended 1/3 of the total length whereas in the X2 chromosome the markings were located around the centromeric region. The markings on autosomal chromosomes were concentrated in the centromeric region in both species, with a heterochromatic block in one arm of chromosome II of A. darlingi. A. nuneztovari had three heterochromatic blocks in chromosome X1 (longer) and two blocks in X2 (shorter). X2X2 females were not detected in either species. The X1 and X2 chromosomes of males were found in A. darlingi, whereas in A. nuneztovari only the X1 chromosome was detected. Only intraspecific variation was found in heterochromatic block markings in the sex chromosomes and autosomes in the two populations of both species at each location. Pela técnica do bandamento C detectou-se variação de marcação dos blocos heterocromáticos dos cromossomos de A. darlingi e A. nuneztovari de Manaus, Amazonas, e de Macapá, Amapá, Brasil. Os cromossomos sexuais de ambas as espécies mostraram duas formas de cromossomos X e o Y foi totalmente heterocromático. No cromossomo X1 de A. darlingi a marcação atingiu 1/3 e no cromossomo X2 foi apenas na região centromérica. Nos autossomos de ambas as espécies as marcações foram constantes nas regiões centroméricas, e o cromossomo II de A. darlingi mostrou um bloco heterocromático em um dos braços. A. nuneztovari mostrou polimorfismo de tamanho para o cromossomo X, tendo o X maior (X1) três blocos e o menor (X2) dois blocos heterocromáticos. Fêmeas homozigotas (X2X2) não foram detectadas nas duas localidades. Em machos de A. darlingi foram encontrados os cromossomos X1 e X2, enquanto que em machos de A. nuneztovari somente o cromossomo X1 foi detectado. Apenas variação intraespecífica de blocos heterocromáticos nos cromossomos X e nos autossomos foi registrada nas duas populações de ambas as espécies estudadas em cada localidade.